2005
DOI: 10.1080/10641950500281209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preeclampsia on Blood Pressure in Newborn Very Low Birth Weight Infants

Abstract: Preeclampsia is associated with higher blood pressure in very low birth weight neonates who are >or= 29 weeks gestation. The long-term significance of this finding is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…However we excluded infants born to mothers with preeclampsia a priori because our own data confirm that they have higher BP than infants born to mothers without preeclampsia. 7 When the analysis was repeated with these infants included (data not presented), the results were unchanged, with the sole exception that the association of FVI with lower BP in the oldest GA stratum was even stronger than reported.…”
Section: Significancementioning
confidence: 85%
See 1 more Smart Citation
“…However we excluded infants born to mothers with preeclampsia a priori because our own data confirm that they have higher BP than infants born to mothers without preeclampsia. 7 When the analysis was repeated with these infants included (data not presented), the results were unchanged, with the sole exception that the association of FVI with lower BP in the oldest GA stratum was even stronger than reported.…”
Section: Significancementioning
confidence: 85%
“…In addition, infants born to mothers with pre-eclampsia were excluded because we have shown that these infants may have elevated BP in the first week of life. 7 BP in the immediate newborn period is tightly correlated with gestational age (GA). 8 Thus, infants were placed into one of three GA stratum: 23 to 26, 27 to 29, and Z30 weeks based on the best estimate of GA. Obstetrical dating was used if an ultrasound was obtained prior to 18 weeks gestation or if the date of the last menstrual period was known.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…The majority of studies (Palti and Rothschild, 1989; Seidman et al, 1991; Tenhola et al, 2003, 2006; Vatten et al, 2003; Swarup et al, 2005; Hiller et al, 2007; Oglaend et al, 2009; Kvehaugen et al, 2010; Lazdam et al, 2010; Palmsten et al, 2010; Lawlor et al, 2012), but not all (Ounsted et al, 1983; Jayet et al, 2010; Belfort et al, 2012; Lawlor et al, 2012) report that children and adolescents who were exposed to preeclampsia or hypertension in pregnancy exhibit higher systolic and diastolic blood pressure compared with non-exposed children or adolescents. These studies were reviewed in a recent meta-analysis (Davis et al, 2012a), which included individuals aged 4–30 years, born at term from preeclamptic pregnancies.…”
Section: Developmental Origins Of Adult Disease After Preeclampsiamentioning
confidence: 99%
“…Maternal morbidity, smoking and medication with indomethacin, MgSo 4 , antihypertensive drugs, e.g. methyldopa, dihydralazine, labetolol and nifedipine were registered, as was administration of antenatal betamethasone for fetal lung maturation [26][27][28][29][30] . Blood pressure was always monitored by an indwelling arterial catheter (umbilical, radial, ulnar or tibial artery) connected to a continuous monitoring system.…”
Section: Methodsmentioning
confidence: 99%